2019
DOI: 10.1097/meg.0000000000001282
|View full text |Cite
|
Sign up to set email alerts
|

Clinical experience with ferric carboxymaltose in the management of anemia in acute gastrointestinal bleeding

Abstract: ObjectiveThe aim of this study was to assess the efficacy and safety of intravenous ferric carboxymaltose (FCM) following hospitalization for acute gastrointestinal bleeding (AGIB) in the context of a restrictive transfusion strategy.Patients and methodsA retrospective single-center study analyzed patients with AGIB (excluding AGIB secondary to portal hypertension) administered a single FCM dose with or without blood transfusion.ResultsEighty-six episodes in 84 patients were analyzed. Seventy-nine patients had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 43 publications
0
23
0
Order By: Relevance
“…Studies comparing iv FCM and oral FeSulf in other indications with acute and chronic blood loss (eg uterine bleeding, postpartum anaemia) using a similar study design as the study presented here showed superiority of FCM in the correction of both anaemia and iron deficiency 10,[28][29][30]. A recently published retrospective analysis reported data from patients with acute GIB who were treated with a single 1000 mg iron dose FCM either alone or combined with red blood cell transfusions (given in patients with Hb <7 g/dL or haemodynamic instability) 26. Patients in both the FCM + transfusion and the FCM alone group recovered from lowest in-hospital Hb levels of 7.2 and 8.8 g/ dL to 9.4 and 9.3 g/dL at discharge and to 12.4 and 13.7 g/dL at 2-month follow-up, suggesting that FCM therapy can facilitate a restrictive transfusion policy.…”
mentioning
confidence: 52%
See 3 more Smart Citations
“…Studies comparing iv FCM and oral FeSulf in other indications with acute and chronic blood loss (eg uterine bleeding, postpartum anaemia) using a similar study design as the study presented here showed superiority of FCM in the correction of both anaemia and iron deficiency 10,[28][29][30]. A recently published retrospective analysis reported data from patients with acute GIB who were treated with a single 1000 mg iron dose FCM either alone or combined with red blood cell transfusions (given in patients with Hb <7 g/dL or haemodynamic instability) 26. Patients in both the FCM + transfusion and the FCM alone group recovered from lowest in-hospital Hb levels of 7.2 and 8.8 g/ dL to 9.4 and 9.3 g/dL at discharge and to 12.4 and 13.7 g/dL at 2-month follow-up, suggesting that FCM therapy can facilitate a restrictive transfusion policy.…”
mentioning
confidence: 52%
“…A recently published retrospective analysis reported data from patients with acute GIB who were treated with a single 1000 mg iron dose FCM either alone or combined with red blood cell transfusions (given in patients with Hb <7 g/dL or haemodynamic instability) . Patients in both the FCM + transfusion and the FCM alone group recovered from lowest in‐hospital Hb levels of 7.2 and 8.8 g/dL to 9.4 and 9.3 g/dL at discharge and to 12.4 and 13.7 g/dL at 2‐month follow‐up, suggesting that FCM therapy can facilitate a restrictive transfusion policy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are a few studies of the efficacy of i.v. FCM in acute or chronic GI bleeding anemia of different etiologies (13)(14)(15)(16)(17), but there are no data on its use in the treatment of anemia after acute or chronic GIB in patients with cirrhosis. Therefore, the objective of our study was to investigate the efficacy and safety of FCM treatment in cirrhotic patients with acute or chronic GIB.…”
Section: Introductionmentioning
confidence: 99%